Network Community Detection on Small Quantum Computers. Issue 9 (3rd June 2019) - Shaydulin, Ruslan; Ushijima‐Mwesigwa, Hayato; Safro, Ilya; Mniszewski, Susan; Alexeev, Yuri
Abstract: In recent years, a number of quantum computing devices with small numbers of qubits have become available. A hybrid quantum local search (QLS) approach that combines a classical machine and a small quantum device to solve problems of practical size is presented. The proposed approach is applied to the network community detection problem. QLS is hardware‐agnostic and easily extendable to new quantum computing devices as they become available. It is demonstrated to solve the 2‐community detection problem on graphs of sizes of up to 410 vertices using the 16‐qubit IBM quantum computer and D‐Wave 2000Q, and compare their performance with the optimal solutions. The results herein demonstrate that QLS performs similarly in terms of quality of the solution and the number of iterations to convergence on both types of quantum computers and it is capable of achieving results comparable to state‐of‐the‐art solvers in terms of quality of the solution including reaching the optimal solutions. Abstract : A hybrid quantum local search (QLS) approach is described. QLS combines a classical machine and a small quantum device. The proposed approach is applied to the network community detection problem to solve the underlying optimization models on graphs of sizes up to 410 vertices using the 16‐qubit IBM quantum computer and D‐Wave 2000Q.